Nick Joaquin Now: Texts, Contexts, and Approaches - Martin, Jocelyn (Archīum Ateneo, 2018)
This Introduction to “Nick Joaquin Now: Texts, Contexts and Approaches” surveys the main critical works on Nick Joaquin’s oeuvre and presents an overview of the essays included in this Forum Kritika. Following the contributions of scholars such as Blanco, E. San Juan, Galdon, Gutierrez, Hau, Holden, Patke, Pison, and Serrano, this new collection of essays reveals novel readers and (re)readings of Joaquin. The editors treat Joaquin “not as an object of study but more as an effect to be explained, where we as ‘readers’ become the implied readers that Joaquin’s works requires.” Following Nick Joaquin’s centennial, marked by, among others, the release of the movie Ang Larawan and the publishing of the Penguin version of his short stories, this Special Issue features Arong’s “Temporality in Nick Joaquin’s The Woman Who Had Two Navels”; Delos Reyes and Selman’s “The Female Monster: The Pre-Catholic Manifestation as a Response to Modern Anxiety in Selected Stories by Nick Joaquin”; Labayne’s “Bedeviling Quijano De Manila’s Discourses of the Devil’s Advocate and the Openness of Historical Interpretation”; and Lizada’s “When She Started Acting Queer: A Queer Gothic Reading of Nick Joaquin’s The Woman Who Had Two Navels.”